Web accessibility of the Malaysian public university websites - Ahmi, Aidi; Mohamad, Rosli (2015)
The accessibility of the Malaysian public university websites is crucial to make sure that all of the staff, students and visitors of the website have equal opportunities to access the university’s information.Furthermore, with the objective to achieve high ranking web of universities or webometrics, it is important that the webmasters of the web to ensure that their web accessibility comply with the standards and guidelines. This paper evaluates the accessibility of the 20 public universities in Malaysia based on the Web Content Accessibility Guidelines (WCAG) 2.0 and Section 508 of the United States Rehabilitation Act. The result suggested that although there are some improvements have been made as compared to the findings from the previous studies, some actions need to be taken to ensure that the universities websites are accessible to everyone regardless of their ability, constraint and limitation. Among the issues that are important to be highlighted include distinguish ability, keyboard accessibility, navigability, adaptability and text alternative for non-text elements.